(untitled) - Lane, Russell W (New York, 1993)
The book includes in-depth coverage of portable and domestic hot water treatment, steam, condensate, and boiler water treatment, air conditioning and water cooling treatment, cloded system water treatment, external water treatment methods, piping, tubing, and plumping systems, and building operations and maintenance. The book also contains a quick-reference glossary of water treatment terms; specifications for water treatment chemicals, test reagents, and testing equipment; and water analytical test methods
Keywords: Pipes, deposits in,Water-pipes,Water-pipes; Corrosion,Maintenance and repair